Clinical course of patients with ALI/ARDS treated with sivelestat: comparison of effects on direct and indirect lung injury using high-resolution CT and clinical parameters - Nakagawa, Yoshihide; Sugiyama, Mitsugi; Inokuchi, Sadaki; Arata, Shinju; Niimi, Hiroshi; Seki, Ippei; Unemoto, Kyoko; Nishimaki, Horoshi; Soma, Kazui; Nakazawa, Akio; Imai, Hiroshi; Kurokawa, Akira; et al. (Nihon Kyukyu Igakukai Zasshi, 2013)
Objective: Patients with acute lung injury (ALI) / acute respiratory distress syndrome (ARDS) accompanied with sepsis were divided into groups with direct and indirect lung injuries. Clinical courses after administration of sivelestat, a selective neutrophil elastase inhibitor, were compared using high-resolution CT (HRCT). Subjects and Methods: The subjects were 20 patients with ALI/ARDS who received HRCT at seven medical emergency care centers in Kanagawa Prefecture from January 2006 to March 2008, and in whom continuous intravenous administration of sivelestat hydrate at a dose of 0.2 mg/kg/hr for 5 days or more was started upon diagnosis. Changes of lung oxygenation and chest X-ray and HRCT findings were evaluated. HRCT findings for consolidation, ground-glass opacity, thickening of the interlobular septum, and traction bronchiectasis were scored, and the clinical courses of patients with direct lung injury (ALI/ARDS due to severe pneumonia) and indirect lung injury (ALI/ARDS due to other infections) were compared to evaluate the effects of sivelestat. Result: The rates of improvement of lung oxygenation in the direct (n=10) and indirect (n=10) lung injury groups were 60% and 100%, respectively, with a tendency for greater efficacy of sivelestat for indirect lung injury. There were no differences in chest X-ray scores, but the “acute-phase” HRCT score (total of the consolidation and ground-glass opacity scores) showed greater improvement in the indirect lung injury group, with strong correspondence to the change in lung oxygenation. Conclusion: Clinical courses in subjects receiving sivelestat were better in those with indirect lung injury compared to cases with direct lung injury. HRCT was found to be useful for determining the pathological stage of ALI/ARDS and the appropriate timing of drug administration.